1999
DOI: 10.1152/ajpendo.1999.276.6.e1083
|View full text |Cite
|
Sign up to set email alerts
|

A marathon run increases the susceptibility of LDL to oxidation in vitro and modifies plasma antioxidants

Abstract: Physical activity increases the production of oxygen free radicals, which may consume antioxidants and oxidize low-density lipoprotein (LDL). To determine whether this occurs during strenuous aerobic exercise, we studied 11 well-trained runners who participated in the Helsinki City Marathon. Blood samples were collected before, immediately after, and 4 days after the race to determine its effect on circulating antioxidants and LDL oxidizability in vitro. LDL oxidizability was increased as determined from a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
92
1
19

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(133 citation statements)
references
References 63 publications
21
92
1
19
Order By: Relevance
“…The rise of total capacity of antioxidants on the third day was probably the result of stabilised conditions associated with the food consumption that allowed an intake of antioxidants. On the other hand, a decrease of total antioxidant capacity observed afterwards, on the seventh day, could reflect physical stress due to increased physical activity of the patients, which may under convalescence resemble intense physical exercise as observed for healthy sportsmen who also exert a decrease in total antioxidant capacity after exercise (Liu et al 1999;Schippinger et al 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The rise of total capacity of antioxidants on the third day was probably the result of stabilised conditions associated with the food consumption that allowed an intake of antioxidants. On the other hand, a decrease of total antioxidant capacity observed afterwards, on the seventh day, could reflect physical stress due to increased physical activity of the patients, which may under convalescence resemble intense physical exercise as observed for healthy sportsmen who also exert a decrease in total antioxidant capacity after exercise (Liu et al 1999;Schippinger et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…However, on the third and the seventh day the measured antioxidant capacity should not be affected much by heparin administered at the time surgical intervention. The increase in the total antioxidant capacity of the sera from the cubital vein on the third day following PCI could also be due to uric acid, which is intensively produced during intensive physical stress and ischemia-reperfusion, as shown in the course of oxidative stress in marathon runners (Liu et al 1999;Waring et al 2003). The rise in antioxidant capacity could also be due to the release of intracellular antioxidants caused by tissue damage during AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (1999) reported that marathon athletes presented increased susceptibility of low density lipoprotein (LDL) cholesterol to peroxidation. They also observed increased levels of both plasma total antioxidant capacity and uric acid, although a significant decrement in potent antioxidant blood thiols also occurred.…”
Section: Total Antioxidant Capacity In Exercise Physiology Studiesmentioning
confidence: 99%
“…Because of its hydrophilic nature and reducing activity, uric acid is considered an important interfering factor in TAC evaluation (Benzie and Strain 1996;Liu et al 1999; Rice-Evans 2000; Neubauer et al 2008). …”
Section: Regular Physical Exercise: Adaptation To Oxidative Stress Anmentioning
confidence: 99%
“…Nevertheless, it is conceivable that the physiological antioxidant response to exercise can be enhanced to prevent or reduce loss of LCAT activity by either scavenging peroxynitrite or reducing ROS formation in the two compartments involved in the reverse cholesterol transport, namely the cell plasma membrane and the lipoprotein. 19 Different concentrations of major antioxidants were previously found before and after long-term exercises, such as marathon 20,21 or an intense physical training 22,23 or consecutive days of exercise. 24 The ergometric test (ET) represents a form of exercise with increasing physical effort and oxygen consumption.…”
Section: Introductionmentioning
confidence: 99%